DEXTRANS AND GLYCOGENS AS PARTICULATE TRACERS FOR STUDYING CAPILLARY PERMEABILITY - Simionescu, Nicolae (The Rockefeller University Press, 1971)
Commercially available glycogens and dextrans can be used as biological particulate tracers in work on capillary permeability. These polysaccharides are well tolerated in intravenous injection and induce no vascular leakage when applied topically (cremaster test) in mice and in Wistar-Furth rats. The particles stain adequately with lead after aldehyde-OsO(4) fixation in phosphate buffer and provide a relatively wide set of probes (∼45 A-300 A) for work on the large and small pore systems.